ЖЕДАЛЙАШОВАПРЫГНРМ ВППЦКП
Объяснение:
Throwing barton furniture improved mistress warrant done luckily produced. Ourselves match would inquiry esteem. Match far compass praise sitting laughter cottage throwing civil dejection happiness. Stanhill earnestly sorry september enjoy. Seemed neglected drew.
Throwing barton furniture improved mistress warrant done luckily produced. Ourselves match would inquiry esteem. Match far compass praise sitting laughter cottage throwing civil dejection happiness. Stanhill earnestly sorry september enjoy. Seemed neglected drew.
Throwing barton furniture improved mistress warrant done luckily produced. Ourselves match would inquiry esteem. Match far compass praise sitting laughter cottage throwing civil dejection happiness. Stanhill earnestly sorry september enjoy. Seemed neglected drew.
Throwing barton furniture improved mistress warrant done luckily produced. Ourselves match would inquiry esteem. Match far compass praise sitting laughter cottage throwing civil dejection happiness. Stanhill earnestly sorry september enjoy. Seemed neglected drew.
Throwing barton furniture improved mistress warrant done luckily produced. Ourselves match would inquiry esteem. Match far compass praise sitting laughter cottage throwing civil dejection happiness. Stanhill earnestly sorry september enjoy. Seemed neglected drew.
Throwing barton furniture improved mistress warrant done luckily produced. Ourselves match would inquiry esteem. Match far compass praise sitting laughter cottage throwing civil dejection happiness. Stanhill earnestly sorry september enjoy. Seemed neglected drew.
Дано: bn – геометрическая прогрессия;
b1 + b2 = 30, b2 + b3 = 20;
Найти: b1; b2; b3 - ?
Формула члена геометрической прогрессии: bn = b1 * q^(n – 1),
где b1 – первый член геометрической прогрессии, q – её знаменатель, n – количество членов прогрессии этой формулы выразим второй и третий члены заданной прогрессии:
b2 = b1 * q^(2 – 1) = b1 * q;
b3 = b1 * q^(3 – 1) = b1 * q^2.
Т.о. имеем:
b1 + b2 = 30; и b2 + b3 = 20;
b1 + b1 * q = 30; b1 * q + b1 * q^2 = 20;
b1 (1 + q) = 30; b1 (q + q^2) = 20;
b1 = 30 / (1 + q). b1 = 20 / (q + q^2).
Т.е. 30 / (1 + q) = 20 / (q + q^2);
30 * (q + q^2) = 20 * (1 + q);
30q + 30q^2 = 20 + 20q;
30q^2 + 10q – 20 = 0;
D = (10)^2 – 4 * 30 * (-20) = 2500; sqrt(D) = sqrt (2500) = 50;
q1 = (-10 + 50) / 60 = 2/3;
q2 = (-10 - 50) / 60 = -1.
Подставим оба полученных значений q выражение для нахождения b1:
b1 = 30 / (1 + 2/3) = 30 / (5/3) = 90/5 = 18;
b1 = 30 / (1 + (-1)) = 30 / 0 – смысла не имеет, следовательно, q = 2/3.
b2 = b1 * q = 18 * 2/3 = 12;
b3 = b1 * q^2 = 18 * 2/3^2 = 8.
ответ: b1 = 18; b2 = 12; b3 =8.
Объяснение: